ANALISIS STAKEHOLDER DALAM PENGELOLAAN BUMDES “SUMBER REJEKI” DESA JIWAN KECAMATAN JIWAN KABUPATEN MADIUN - M. Husni Tamrin; Liliana Rifti (Jurnal Ilmiah Wahana Bhakti Praja, 2023)
Village-owned enterprises that are advanced in management require attention to the support and participation of each of the stakeholders involved. The role of stakeholders in the management of BUMDes "Sumber Rejeki" Jiwan Village, Madiun Regency is very necessary so that the development of BUMDes can run effectively and efficiently. This study aims to identify and obey the roles of each stakeholder involved based on the level of "influence" and the level of "interest" of stakeholders. The method used in this research is descriptive qualitative method. The results of the study are that the stakeholders involved are primary stakeholders consisting of DPMD of Madiun Regency, Head of BUMDes "Sumber Fortune", the people of Jiwan Village, Key stakeholders consist of the Head of Jiwan Village, while secondary stakeholders consist of BRI Bank Jiwan Unit and BPR Polatama Kusuma. The group that has a high value of influence and interest is on the keyplayers, namely the Head of Jiwan Village and the Head of Bumdes "Sumber Fortune". The roles of each stakeholder include being a coordinator, implementer, policy creator and facilitator. Those who do not carry out the role of BUMDes management "Sumber Fortune" are the DPMD of Madiun Regency